Memahami Makna : Kaidah ‘Amm dan Khash Serta Amr dan Nahi dalam Ushul Fiqih - A. Adillah Zahiyah Djaka; Adelia Nurinsan; Muhammad Aldi Dahr; Kurniat Kurniat (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Rules in Islam such as Amm and Kash as well as Amr and Nahi are used to understand Islamic law. Where these rules are the basis of Ushul fiqih, which discusses the methodology of determining Islamic law. This study uses a literature research method to understand how these rules are used to understand amm and kash as well as amr and nahi in Ushul fiqih. This data is collected from various written sources such as books, journals, literature and scientific publications. The rule of 'amm and kash' is used to understand the verses of the Qur'an and Hadith. "Amm means general rules and kash means special rules. " Therefore, these rules help determine the laws that apply in general and specifically in Islam. For example, the rule of "amm" can be used to understand verses that are generally applicable to all Muslims, while the rule of khash can be used to understand verses that apply specifically to certain situations. Amr and Nahi are used in understanding Islamic law. Amr means command and nahi means prohibition. These rules are crucial in determining which laws to follow or avoid in Islam. For example, amr can be used to understand the command to pray, and nahi can be used to understand the prohibition of adultery. The results of this study show that the rules of "Amm, Khash, Amr, and Nahi" are very important in enforcing Islamic law. An in-depth study of these rules will help to understand the meaning of sharia statements (Al-Quran and Hadith) more accurately and comprehensively. Misunderstandings in interpreting sharia provisions can be fatal. Therefore, understanding these rules is an important means of avoiding misinterpretation or misleading. This study will also enrich the treasures of Islamic science, especially in the field of Ushul fiqh and Islamic Law. Understanding these rules will help Muslims gain a deeper and more comprehensive understanding of their religious teachings and enable them to practice them more accurately and responsibly. Therefore, this research will help Muslims to face various situations and problems in daily life more wisely.